Cannabidiol induces autophagy via ERK1/2 activation in neural cells - Talita A. M. Vrechi (Nature Portfolio, 2021)
Abstract Autophagy is a lysosomal catabolic process essential to cell homeostasis and is related to the neuroprotection of the central nervous system. Cannabidiol (CBD) is a non-psychotropic phytocannabinoid present in Cannabis sativa. Many therapeutic actions have been linked to this compound, including autophagy activation. However, the precise underlying molecular mechanisms remain unclear, and the downstream functional significance of these actions has yet to be determined. Here, we investigated CBD-evoked effects on autophagy in human neuroblastoma SH-SY5Y and murine astrocyte cell lines. We found that CBD-induced autophagy was substantially reduced in the presence of CB1, CB2 and TRPV1 receptor antagonists, AM 251, AM 630 and capsazepine, respectively. This result strongly indicates that the activation of these receptors mediates the autophagic flux. Additionally, we demonstrated that CBD activates autophagy through ERK1/2 activation and AKT suppression. Interestingly, CBD-mediated autophagy activation is dependent on the autophagy initiator ULK1, but mTORC1 independent. Thus, it is plausible that a non-canonical pathway is involved. Our findings collectively provide evidence that CBD stimulates autophagy signal transduction via crosstalk between the ERK1/2 and AKT kinases, which represent putative regulators of cell proliferation and survival. Furthermore, our study sheds light on potential therapeutic cannabinoid targets that could be developed for treating neurodegenerative disorders.